Concomitant opioid and benzodiazepine use and risk of suicide attempt and intentional self-harm: Pharmacoepidemiologic study. (1st November 2021) - Gibbons, Robert D.; Hur, Kwan; Quinn, Patrick D.
Abstract: Background: Overdose due to concomitant use of opioids and benzodiazepines has been raised as a major public health concern, although little research has examined whether this risk extends to intentional overdose or other self-harm. This study examined whether prescription opioids and benzodiazepines interact to increase the rate of suicide attempt and intentional self-harm. Methods: The study analyzed 4, 762, 438 users of opioids, benzodiazepines, both drugs concomitantly, or neither drug from the MarketScan Commercial Claims and Encounters databases (2014–2016). The four groups were matched using inverse probability of treatment weighting and a difference in difference design was used to examine associations with risk of suicide attempt, intentional self-harm and drug overdose, including suicide death resulting in a medical claim. Results: There was a small association for opioids (HR=1.23; 95% CI 1.06–1.43) but a larger association for benzodiazepines (HR=2.55; 95% CI 2.12–3.05) with suicide attempt, intentional self-harm, and drug overdose. The medication interaction was opposite to the expected direction (HR=0.70; 95% CI 0.55–0.89), indicating that risk associated with concomitant use was lower than would be expected on an additive basis. Sensitivity analyses found no evidence of increased risk due to interaction between the two drug classes. Conclusions: Increased risk of suicide attempt, intentional self-harm and drug overdose for concomitant use of opioids and benzodiazepines is in large part attributable to benzodiazepine use alone. In typically prescribed quantities, opioids and benzodiazepines may not represent a drug interaction in terms of yielding increased risk of suicide attempt and intentional self-harm resulting in medical care. Highlights: Concomitant opioid and benzodiazepine use is associated with increased risk of suicide attempt and self-harm. Examined suicide risk and self-harm by overdose and did not find evidence of a drug interaction. Increased risk of suicide attempts and self-harm is driven predominantly by benzodiazepines.